How does urbanization affect the direct rebound effect? Evidence from residential electricity consumption in China. (15th January 2022) - Shi, Jian-hua; Han, Ying; Li, Xue-dong; Zhou, Jie-qi
Abstract: The direct rebound effect offsets part of energy savings brought about by energy efficiency, causing academics and governments to re-examine the relationship between energy efficiency and conservation. Although suppressing the rebound effect contributes to energy conservation, how to implement it is debatable. This paper puts forward a framework to character the direct rebound effect, and develops non-linear models to explore the impacts of urbanization on the direct rebound effect based on a panel dataset of 30 Chinese provinces. The results show that, first, the magnitude of the direct rebound effect is much smaller in urban areas than that in rural areas. Second, urbanization could restrain the direct rebound effect in urban areas, where employment and environmental consciousness play important roles while the impact of agglomeration is relatively weak. The impacts of urbanization on direct rebound effect are not substantial in rural areas. In addition, our findings reject the saturation effect caused by income. Income promotes the direct rebound effect in rural areas while it could not restrain the direct rebound effect in urban areas. Therefore, the reason that the average direct rebound effect tends to decline with income growth seems to be the urbanization rather than the saturation effect. Highlights: This paper puts forward a framework to character the RE and explore its evolution. A new urbanization that looks at its quality rather than its growth is conducted in this paper. The relationship between income and the RE is re-examined and it has the urban-rural heterogeneity. The RE of urban areas decreases with urbanization mainly in the employment and environment dimensions.